2018
DOI: 10.4103/picr.picr_41_17
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of change in knowledge about research methods among delegates attending research methodology workshop

Abstract: Aim:In an era of evidence based medicine research is an essential part of medical profession whether clinical or academic. A research methodology workshop intends to help participants, those who are newer to research field or those who are already doing empirical research. The present study was conducted to assess the changes in knowledge of the participants of a research methodology workshop through a structured questionnaire.Methods:With administrative and ethical approval, a four day research methodology wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…The present study revealed the pre-test knowledge was not suf icient for patient care; therefore, the regular training program may be improved health care workers' knowledge on COVID-19. Our study also found that the teaching session was bene i- cial for inal year BSc nursing students (Shrivastava et al, 2018;Thakre, 2020). The mean difference in pre-test and post-test-2,3.92,5.02 & 1.1, respectively.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The present study revealed the pre-test knowledge was not suf icient for patient care; therefore, the regular training program may be improved health care workers' knowledge on COVID-19. Our study also found that the teaching session was bene i- cial for inal year BSc nursing students (Shrivastava et al, 2018;Thakre, 2020). The mean difference in pre-test and post-test-2,3.92,5.02 & 1.1, respectively.…”
Section: Resultssupporting
confidence: 66%
“…Many studies supported inding that health workers have good knowledge of 93%), and most of them have a lack of emotional con idence. Hence fore continue education and counselling may improve their mental health (Maleki, 2020;Shrivastava et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The results are comparable with the similar findings conducted by Shrivastava et al which showed pre and post test were effective way of assessing as well as creating awareness among the participants. 11 …”
Section: Discussionmentioning
confidence: 99%
“…The minimum required sample size calculated using University of California San Francisco Calculator [20] was 161, with alpha 0.05, beta 0.20, effect size 0.500, and standard deviation (SD) of the post-over-pre change of 2.25. The SD was calculated using the following formula from a previously published study with a similar study design [21], with standard error of mean (SEM) 1 and 2 computed from SD on the pre-test (16.11%) and post-test (12.39%), respectively.…”
Section: Participant Recruitment and Enrolmentmentioning
confidence: 99%